Mining Hazards to the Safety of Segment Lining for Tunnel Boring Machine Inclined Tunnels - Zhuo, Hui; Xie, Dan; Sun, Jinglai; Shi, Xiaomeng (Frontiers in Earth Science, 2022)
The segment lining is a new type of support structure for mining tunnels. The disturbance of coal excavation leads to the deformation of segment lining and has great hazards to the safety of the tunnels. Based on the TBM inclined tunnels in Xinjie mine, the ultimate span L0 of the rock beam on the top slab of the coal seam was calculated according to the bending (tension) damage theory. A numerical model was built to simulate the bottom area of the inclined tunnels. During the coal mining, the additional displacements and additional stresses of the segment lining were analysed, and then the safety factors of the support structure were calculated. Finally, the width of the coal pillar to protect the inclined tunnels was determined. The results showed that the ultimate span of the rock beam on the top of the coal seam is 31.7m, the deformation of the inclined tunnel has a fish-belly shape, and the deformation leads to the increasing of maximum axial force and bending moment. For the inclined tunnels in Xinjie coalmine, a total width of 91.3 m of coal pillar must be reserved to keep the safety factor of the structure higher than 2.0 and prevent the inclined tunnels from the mining hazards.